Thoracoschisis with limb agenesis - Nirmal C Bhattacharyya; Manoj Gogoi; Pradip K Deuri (Wolters Kluwer Medknow Publications, 2012)
A rare case of thoracoschisis, diaphragmatic and supraumbilical abdominal wall defect with right upper limb agenesis in a neonate is reported.